2015
DOI: 10.1007/978-3-319-25210-0_16
|View full text |Cite
|
Sign up to set email alerts
|

ReCon: An Online Task ReConfiguration Approach for Robust Plan Execution

Abstract: The paper presents an approach for the robust plan execution in presence of consumable and continuous resources. Plan execution is a critical activity since a number of unexpected situations could prevent the feasibility of tasks to be accomplished; however, many robotic scenarios (e.g. in space exploration) disallow robotic systems to perform significant deviations from the original plan formulation. In order to both (i) preserve the "stability" of the current plan and (ii) provide the system with a reasonabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Strategy Repair is very related to the notion of plan repair, originally introduced (as plan reuse) in Classical Planning, by [13]. While in that work it is shown that repairing is not more efficient, in general, than replanning, the former exhibits higher effectiveness in practice [10,17]. Surprisingly, while the problem is actively studied in this context , we could not find analogous contributions in the context of Fully Observable Nondeterministic (FOND) Planning, where plans are replaced by policies.…”
Section: Introductionmentioning
confidence: 99%
“…Strategy Repair is very related to the notion of plan repair, originally introduced (as plan reuse) in Classical Planning, by [13]. While in that work it is shown that repairing is not more efficient, in general, than replanning, the former exhibits higher effectiveness in practice [10,17]. Surprisingly, while the problem is actively studied in this context , we could not find analogous contributions in the context of Fully Observable Nondeterministic (FOND) Planning, where plans are replaced by policies.…”
Section: Introductionmentioning
confidence: 99%